Bibliometric analysis of immunotherapy for head and neck squamous cell carcinoma - Xin-Jia Cai; He-Yu Zhang; Jian-Yun Zhang; Tie-Jun Li (Journal of Dental Sciences, 2023)
Background/purpose: Head and neck squamous cell carcinoma (HNSCC) is a serious disease endangering the health of patients, and the application of immunotherapy in HNSCC is gradually emerging. However, there is no bibliometric analysis in this research field. This study aims to provide a comprehensive overview of the knowledge structure and research hotspots of immunotherapy for HNSCC. Materials and methods: Publications related to immunotherapy for HNSCC from 2002 to 2021 were searched in the Web of Science Core Collection database. The software VOSviewers, CiteSpace, and the R package ‘bibliometrix’ were used to perform this bibliometric analysis. Results: A total of 1297 publications were from 63 countries, led by the USA and China. The number of publications related to immunotherapy for HNSCC has increased rapidly from 2015. University of Pittsburgh and The University of Texas M.D. Anderson Cancer Center are the main research institutions. Oral Oncology is the most popular journal in this field, and the Journal of Clinical Oncology is the most highly co-cited journal. These publications were from 7569 authors, with Robert L. Ferris publishing the most papers and being the most frequently co-cited. Clinical trials related to nivolumab and pembrolizumab have attracted wide attention. ‘Immune checkpoint inhibitors’, ‘human papillomavirus’, ‘programmed cell death-ligand 1’, and ‘programmed cell death protein 1’ are the main keywords of emerging research hotspots. Conclusion: This study presents a comprehensive summary of the trends and development of immunotherapy for HNSCC, identifies the research frontier and hotspot direction, and could provide a valuable reference for researchers in this field.